2021
DOI: 10.1108/arla-01-2021-0020
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and higher education: responding to local demands and the consolidation of e-internationalization in Latin American universities

Abstract: PurposeThis paper aims to provide insights into the internationalization strategic responses to the COVID-19 pandemic by higher education institutions (HEIs) in Latin America.Design/methodology/approachThis study is based on information from eight leading Latin American private universities. The data were obtained from official sources such as institutional communications and university administrators.FindingsThe authors identify two main issues that HEIs should consider while responding to the pandemic. First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 35 publications
1
31
0
2
Order By: Relevance
“…The contemporary HEI operates within a globalized milieu, populated by citizens from a diverse range of cultural and ethnic backgrounds (Cordova et al. , 2021; Gonzalez-Perez et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The contemporary HEI operates within a globalized milieu, populated by citizens from a diverse range of cultural and ethnic backgrounds (Cordova et al. , 2021; Gonzalez-Perez et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior research has shown the positive impact of USR on student loyalty (El-Kassar et al. , 2019), on university reputation (Cordova et al. , 2021; Gonzalez-Perez et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations